Is endoscopic endonasal transsphenoidal surgery increases the susceptibility to rhinosinusitis - BİNNETOĞLU, ADEM; BUĞDAYCI, ONUR (SPRINGER, 2017)
The aim of the study was to analyze whether the measurement of changes in the anatomical position and volume of middle concha, the volume changes in the area between the middle concha and lamina papyracea, the evaluation of opacification in major paranasal sinuses, and osteomeatal complex occlusion in cases with middle concha by out-fracture technique during endoscopic endonasal transsphenoidal approach is a minimally invasive surgery, and also to find out whether these changes lead to the development of tendency to rhinosinusitis. It was a retrospective clinical study. Forty-five cases, between 2013 and 2015, planned for endoscopic endonasal transsphenoidal surgery due to hypophyseal pathology at the Neurosurgery Departments of Marmara University Hospital were evaluated retrospectively. The patients were evaluated for the changes in the anatomy of the middle concha and the effects of these changes to paranasal sinuses by paranasal computed tomographies were studied at the preoperative second week and postoperative 12 month. The Lund-Mackay scoring system was used for the evaluation of opacification in the five major paranasal sinuses and occlusion of the osteomeatal complex in the pre- and postoperative period. The Lund-Mackay scoring system was used to analyze the paranasal computed tomography of the patients at the preoperative 2 weeks and postoperative first year. According to the Lund-Mackay scoring system, no significant difference was detected between the preoperative and postoperative opacification of paranasal sinuses (p > 0.05). Besides, there was also no significant difference between the preoperative and postoperative osteomeatal complex occlusion (p > 0.05). Considering the distance between middle concha and lamina papyracea following the out-fracture of the middle concha, a significant lateralization of 0.5 mm between the preoperative and postoperative period was observed (p < 0.05). In addition, a significant change was also detected in the volume of middle concha (p < 0.05). The volume of the area between the middle concha and lamina papyracea was decreased with a statistical significance (p < 0.05). The endoscopic endonasal transsphenoidal surgery causes some variations in the structures of the middle concha, paranasal sinuses, and OMC, but these changes do not lead to significant rhinologic pathologies.
Keywords: Middle concha lateralization; Endoscopic endonasal transsphenoidal surgery; Pituitary surgery; Rhinosinusitis; PITUITARY-GLAND; SINUSITIS; ANATOMY; SELLA